Antioxidant Activity Screening of Callophyllum inophyllum Linn. Seed Fractions - Siti Nurhaliza; Baiq Maylinda Gemantari; Yuyun Febriani (Healthy-Mu Journal, 2023)
Calophyllum inophyllum Linn. known as nyamplung is one of tropical plants widely grown in Indonesia. This plant reported has various chemical compound responsible to treat various deseases and disorders. Antioxidant activity is one of properties that has not been revelad extensively. This study aimed to evaluate antioxidant activity of Calophyllum inophyllum seed fractions using DPPH radical scavenging. Fractination was done gradually by liquid-liquid partition using N-hexane, ethyl acetate and aquadest as solvent. The phytochemical contents of each fraction were analyzed using AlCl3, FeCl3 and Lieberman-Burchard as dyeing reagents. Antioxidant activity was evaluated qualitative and quantitatively. The obtained results showed that N-hexane, ethyl acetate and aquadest fractions contained flavonoids, phenolics, terpenoid and steroid compound. All fractions also revealed antioxidant properties. Quantitatively, N-hexane fraction has the strongest anioxidant properties. This result might imply due to non-polar compound in the seeds dominantly.